2021
DOI: 10.1007/s40171-020-00257-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Information Flow Characteristics in Shop Floor: State-of-the-Art and Future Research Directions for Developing Countries

Abstract: The information flow in a company is a whole set of static or dynamic data obtained from communication used for the conception and realization of products; facing competition, every company aims at improving its performance to meet customer needs. The focus on information flow to improve the performances of companies has always been a major preoccupation in the research domain, which always contributes to the evolution of the analysis of information flow for companies to be more efficient. This article present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Data is collected through documentation and interviews, including an interview with one of the people from the freight forwarding company, which provides company information and petty cash data. The flow of the goods delivery recapitulation system in the company was also analyzed (Mbakop et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Data is collected through documentation and interviews, including an interview with one of the people from the freight forwarding company, which provides company information and petty cash data. The flow of the goods delivery recapitulation system in the company was also analyzed (Mbakop et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The software that has been designed to manage static information in well-organized production companies cannot perform the same tasks on the SF of developing countries where information flow is dynamic and does not sometimes respect specific criteria of flow. This situation is presented in Figure 1 by Mbakop et al. (2021) .…”
Section: Introductionmentioning
confidence: 84%
“…The characterization of information flow aims to know in detail what makes an information flow not useful in a production operation. The CIF globally presented by Mbakop et al (2021) is shown in Figure 2. The characterization of the information flow in the SF is based on the following:…”
Section: Characteristics Of Information Flowmentioning
confidence: 99%